Colorimetric determination of food colourants using solid phase extraction into polymethacrylate matrix; Talanta; Vol. 202 - Dudkina A. A. Anna Aleksandrovna; Volgina T. N. Tatiana Nikolaevna; Saranchina N. V. Nadezhda Vasilievna; Gavrilenko N. A. Natalia Airatovna; Gavrilenko M. A. Mikhail Alekseevich (2019, 2019)
Title screen